USE OF COMPUTER TECHNOLOGIES TO STUDY ERRORS AND COMPLICATIONS IN DENTAL IMPLANTOLOGY (World Bulletin of Public Health, 2026)
This paper examines the problems of errors and complications arising during dental implantation, which has become widespread in dental practice in recent years. The constantly growing demand for implant treatment requires further improvement of planning and implementation methods. However, a misconception has developed in the professional community about the simplicity and universal accessibility of implant procedures, which often leads to complications and, consequently, conflicts between doctor and patient. One effective way to improve the quality of implant treatment is through a systematic and objective analysis of errors, complications, and unsuccessful outcomes. In this regard, the authors developed a specialized computer database designed to accumulate and analyze data on dental implant complications. The resulting information is used in the educational process for students of dental faculties, as well as for doctors undergoing advanced training and professional retraining. The algorithm for the computerized complication analysis program is based on a modern classification system, including intraoperative, early and late postoperative complications, as well as disorders associated with the prosthetic stage and implant use.
Keywords: dental implantation; errors and complications in implant treatment